Inclusive Wealth With Total Factor Productivity: Global Sustainability Measurement - Managi, Shunsuke; Jumbri, Isma Addi (Cambridge University Press, 2020)
Non-technical abstract Wealth commonly refers to the measure of the value of all assets or capital owned by an individual, community, company or nation. Sustainable development requires that the per capita productive base or comprehensive wealth of an economy should at least not decline over a period of time. We present here a comprehensive assessment of cross-country productivity over a study period of 1990–2010 for 140 countries. We used the concept of inclusive wealth introduced by the United Nations to assess the social value, rather than dollar price, of all each country’s assets, including produced, human and natural capital. Technical abstract This study extends the current measures of sustainability using inclusive wealth by capturing total factor productivity (TFP), which takes natural capital and other conventional inputs into consideration. For the inclusive wealth adjustment, we utilized the Malmquist Productivity Index to measure cross-country productivity over a study period of 1990–2010 for 140 countries. We found that incorporating TFP with natural capital has a significant impact on inclusive wealth as a sustainability measure. Natural capital, including oil capital gain related to the change in oil prices, also has a significant role to play in determining the productivity value of a country. In several countries, the decline in natural capital is not high enough to compensate for the increase in both human and produced capital. This finding enhances our understanding of how inclusive wealth adjusted by TFP can be considered as an economic policy evaluation and planning tool regarding countries’ sustainability. Social media summary Sustainability can be assessed by non-declining inclusive wealth, which refers to produced, human and natural capital.